Brand equity of Compass rebranding - Wiraputra, Rafif; Kusumawati, Nurrani (Journal of Business and Management, 2020)
Abstract. The growth of sneakers is followed by the rise of Indonesian sneakers market, as local brands are competing to show and improve their quality, and one of them is Compass. Compass is a local sneakers brand that was founded in 1998, but they had a financial crisis and rebrand in June 2018. Rebranding aims to create new values and perception by customers towards the brand, and rebranding can be said to be successful if customers have a good perception of quality. Aligned with that, brand equity will increase as the value of the brand ncreases, which will increase customer perception towards the brand. This research aims to determine the influence of rebranding and perceived quality on Compass’s brand equity. Therefore, to gain the best results, the researcher has determined several variables to support this research. Data collection is gathered by questionnaire, questionnaire items are based on theory and previous research and distributed through Google Forms. Data were gathered from 415 respondents and will be analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results showed that both of rebranding and perceived quality have significant influence on brand equity.Keywords: Sneakers industry, brand equity, rebranding, perceived quality, PLS-SEM.